Stalin's Claws From the Purges to the Winter War: Red Army Operations Before Barbarossa 1937-1941. - Hooton, E. R. (Tattered Flag, 2013)
""In the late 1930s the Soviet Union experienced a brutal Ezhovshchina - or Purge - which swept through all levels of its society with millions arrested and tens of thousands shot for reasons lacking any form of ethics or justification.As historian, E.R. Hooton describes in this absorbing and revealing history, the Soviet armed forces did not escap""